Government Offices, The Red House, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Exterior view of a government building in Trinidad popularly known as the "Red House", since 1897, where the Trinidad and Tobago Parliament meets. It is of the Greek revival style of architecture and surrounded by trees and other greenery.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Red House, The